Liberalisation and international cooperation - Claus Köhier (Intereconomics, 1988)
While being a necessary consequence of the ongoing and desirable process of international division of labour, the increasing freedom of international money and capital movements has in recent years impaired the efficiency of national economic policy instruments. In order to overcome this drawback the loss in national economic policy autonomy should be counterbalanced by a gain in economic policy cooperation between the national economies.
Keywords: 330; Monetary Policy